2023
DOI: 10.1007/s00590-023-03540-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal-on-metal metaphyseal and ceramic-on-ceramic femoral neck arthroplasty: the impact on clinical results, oxidative stress and concentration of metal ions in serum and blood

Abstract: Purpose Growing number of hip arthroplasty in Poland performed with the use of metaphyseal stems results from the decreasing age of patients qualified for procedures and is consistent with the corresponding trends in European countries. To this day, a significant population functions after undergoing hip replacement using metal-on-metal implant. This study was aimed at the assessment of the variability of the oxidative system, as well as the concentrations of chromium and cobalt ions in serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In a patient undergoing hip replacement revision with elevated blood and urinary concentrations of Cr and Co, an association was reported between metallosis and increased expression of NADPH-Oxidase 4 (NOX4), a well-known compound responsible for ROS generation in muscle tissue [23]. Other studies have suggested a relationship between metallosis and oxidative stress [24,25,59]. According to these reports, our initial hypothesis was that the patients with M-M, with higher Cr and Co levels than the C-M group and the control group, should have greater systemic oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a patient undergoing hip replacement revision with elevated blood and urinary concentrations of Cr and Co, an association was reported between metallosis and increased expression of NADPH-Oxidase 4 (NOX4), a well-known compound responsible for ROS generation in muscle tissue [23]. Other studies have suggested a relationship between metallosis and oxidative stress [24,25,59]. According to these reports, our initial hypothesis was that the patients with M-M, with higher Cr and Co levels than the C-M group and the control group, should have greater systemic oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which toxicity is mediated is still not well understood, nor is the reason why some patients have higher levels than others regardless of renal function. Chromium (Cr) and Co-as redox-active metals-have been shown to be a source of reactive oxygen species (ROS) and various in vitro and in vivo evidence suggests that the toxicity is mediated by the production of ROS and, consequently, oxidative stress [23][24][25][26]. ROS are highly reactive molecules containing oxygen, such as free radicals, generated during cellular processes like metabolism.…”
Section: Introductionmentioning
confidence: 99%